Does access to small scale irrigation promote market oriented production in Ethiopia? - Hagos, Fitsum; Makombe, Godswill; Namara, Regassa E.; Awulachew, Seleshi Bekele (2008)
The study examined the extent and nature of market oriented production in irrigated compared to rainfed systems in Ethiopia. By doing so the paper identifies the role of irrigation in market-oriented production, while at the same time highlighting the main constraints to market oriented development. Our results indicate that irrigation contributes significantly to increases in market participation, volume of marketed produce and, hence, income, by inducing shifts in farmers? cropping mix. The impact of commercialization of production on household food security is not direct and immediate mainly because of failures in the food market. While irrigation enhances market production, there are series of factors that pose serious constraints to market production. Land size, oxen holding, access to market and means of transport were found to be important determinants of market oriented production calling for policy interventions in land markets, access to productive assets and infrastructure development and policy measures to improve the performance of agricultural markets. The study also found education has market promoting effect in terms of increasing the probability of participation and volume of sale. Increased support to education can, thus, help in the long-term to transform traditional subsistence agriculture into more market-oriented agriculture. Finally there are unobserved site specific effects, related to location and other covariates, which influence market participation and volume decisions.